1979
DOI: 10.4095/307131
|View full text |Cite
|
Sign up to set email alerts
|

CANMET's rock mechanics research at the Kidd Creek mine

Abstract: The Kidd Creek mine of Texasgulf Metals Company started as an open pit and later converted to an underground operation. In 1972, a cooperative rock mechanics research project was initiated between the company and the Mining Research Laboratories of CANMET. Research was concerned with stability of the hanging wall pit slope as it was undercut by the underground operations and with ground control aspects of the blasthole open stoping method employed underground. Geotechnical investigations on critical joint orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, surface impact from underground mining activity is very well known and reasonably well understood, as a result of the effect of underground mining activities; many hazards, undesired structural and environmental problems on the surface are being addressed in many countries. Many case studies are reported related to the impact of the underground mining activities, such as Crane (1929), Allen (1934), Rice (1934), Hedley et al (1979), Robertson and Kirsten (1984), Whittaker and Reddish (1989), Charette and Hamel (1993), Wang et al (1995), Betournay (1994Betournay ( , 1995Betournay ( , 2002, Betournay and Wang (1997), Perski and Jura (2003), Marschalko (2004), Marschalko (2011a, b, c), Malgot and Baliak (2004), etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, surface impact from underground mining activity is very well known and reasonably well understood, as a result of the effect of underground mining activities; many hazards, undesired structural and environmental problems on the surface are being addressed in many countries. Many case studies are reported related to the impact of the underground mining activities, such as Crane (1929), Allen (1934), Rice (1934), Hedley et al (1979), Robertson and Kirsten (1984), Whittaker and Reddish (1989), Charette and Hamel (1993), Wang et al (1995), Betournay (1994Betournay ( , 1995Betournay ( , 2002, Betournay and Wang (1997), Perski and Jura (2003), Marschalko (2004), Marschalko (2011a, b, c), Malgot and Baliak (2004), etc.…”
Section: Introductionmentioning
confidence: 99%